Elderly attention to Health strategy in the Family: action of nurses - Oliveira, Juliana Costa Assis de; Tavares, Darlene Mara dos Santos (Revista da Escola de Enfermagem da USP, 2010)
This study aimed to describe the nursing consultation for the elderly provided at the Family Health Strategy (ESF, acronym in Portuguese); identify possible difficulties in delivering health care to the elderly, as well as the professional qualification courses performed and the learning needs. Data were collected through semi-structured interviews and submitted to descriptive and thematic analysis. Interviews were performed with 12 nurses, most with ages between years since graduation (41%) in private institutions (75%). Two thematic categories emerged from the analysis: nursing consultation for the elderly performed at ESF and professional qualification in health care for the elderly. Obtaining reliable data in the nursing consultation, resolution and family support were considered as challenges. The courses to qualify professionals for elderly care occurred during their graduation course, highlighting the lack of opportunity, the short supply and the need for deeper studies about the aging process.